Attenuation of graft‐versus‐host‐disease in NOD scid IL‐2Rγ−/− (NSG) mice by ex vivo modulation of human CD4+ T cells. Issue 9 (25th August 2016) - Hilger, Nadja; Glaser, Jakob; Müller, Claudia; Halbich, Christoph; Müller, Anne; Schwertassek, Ulla; Lehmann, Jörg; Ruschpler, Peter; Lange, Franziska; Boldt, Andreas; Stahl, Lilly; Sack, Ulrich; et al.
Abstract: NOD.Cg‐Prkdc scid IL‐2rg tm1Wjl /SzJ (NSG) mice are a valuable tool for studying Graft‐versus‐Host‐Disease (GvHD) induced by human immune cells. We used a model of acute GvHD by transfer of human peripheral blood mononuclear cells (PBMCs) into NSG mice. The severity of GvHD was reflected by weight loss and was associated with engraftment of human cells and the expansion of leukocytes, particularly granulocytes and monocytes. Pre‐treatment of PBMCs with the anti‐human CD4 antibody MAX.16H5 IgG1 or IgG4 attenuated GvHD. The transplantation of 2 × 10 7 PBMCs without anti‐human CD4 pre‐treatment induced a severe GvHD (0% survival). In animals receiving 2 × 10 7 PBMCs pre‐incubated with MAX.16H5 IgG1 or IgG4, GvHD development was reduced and survival was increased. Immune reconstitution was measured by flow cytometry and confirmed for human leukocytes (CD45), CD3 + /CD8 + cytotoxic T cells and CD3 + /CD4 + T helper cells. Human B cells (CD19) and monocytes (CD14) could not be detected. Histopathological analysis (TUNEL assay) of the gut of recipient animals showed significantly less apoptotic crypt cells in animals receiving a MAX.16H5 IgG1 pre‐incubated graft. These findings indicate that pre‐incubation of an allogeneic graft with an anti‐human CD4 antibody may decrease the frequency and severity of GvHD after hematopoietic stem cell transplantation (HSCT) and the need of conventional immunosuppressive drugs. Moreover, this approach most probably provides a safer HSCT that must be confirmed in appropriate clinical trials in the future. © 2016 International Society for Advancement of Cytometry